Kinetic factors control trace element and isotope zoning in Archean pyrite corona nodules. (15th December 2021) - Chen, Mimi; Campbell, Ian H.
Abstract: Pyrite corona nodules from the ∼2.7 Ga Kapai Slate, a thin, sulfidic carbonaceous shale horizon interbedded with basaltic lava flows in the Yilgarn Craton, Western Australia, have concentric compositional and isotopic zoning with distinctive textural differences between cores and mantles. The sieved-textured cores are enriched in highly compatible trace elements, incl. Ni, As, Ag, Te, Sb, Bi and Pb, and depleted in incompatible Mo and Tl, whereas the radiating-textured mantles are strongly depleted in compatible elements and enriched in incompatible elements, relative to the cores. A striking feature of the data is that both the compatible and incompatible elements are linearly correlated, with correlation coefficients as high as 0.99. A marked drop in the concentration of compatible elements and an increase in incompatible elements at the core-mantle boundary is attributed to a sudden change in the rate of growth of the nodules produced by eruption of the voluminous overlying Paringa Basalt. The weight of the basalt produced sudden compaction of the unconsolidated clays below resulting in upward advection of pore fluid, which thinned the boundary layer around the growing nodules, leading to a marked increase in the rate of pyrite growth. Rapid pyrite growth led to a dramatic depletion in highly compatible elements, and to a build-up in incompatible elements, in the boundary layers around the growing nodule mantles, which resulted in extreme depletion of compatible elements, and enrichment in incompatible elements in the nodule mantles, relative to the cores. The corona nodules are also isotopically zoned with cores that have higher δ 34 S, with small positive Δ 33 S values, and mantles that have lower δ 34 S and higher Δ 33 S. The increase in Δ 33 S towards the rims is attributed to S8 being advected to the growing mantles by upward fluid movement during sudden compaction, and the decrease in δ 34 S to the lighter S isotope, with its higher reactivity and diffusivity, being preferentially incorporated into the fast growing pyrite mantle. The extreme changes in the growth rates of the Kapai Slate corona pyrite nodules provide a new constraint on the partition coefficients of the trace elements between Archean ocean water and sedimentary pyrite. The compatibility of the analysed trace elements decreases in the order Bi > Te > Sb > Ag > Cu > Pb > Ni ≈ As > (Co, Zn, Se, Cd, Mn, W) > Tl > Mo, which is consistent with the order obtained from modern sedimentary pyrites by Large et al. (2014), except for the redox-sensitive elements Mn, Tl and Mo. These differences are attributed to the lower oxygen content of the Archean atmosphere and oceans.